Laparoendoscopic single site adrenalectomy: initial results of cosmetic satisfaction and the potential for postoperative pain reduction - Sasaki, Akira (BioMed Central, 2013)
BACKGROUND: Recent reports have suggested that laparoendoscopic single site (LESS) surgery is technically feasible. The aim of this study was to describe our initial experience with LESS adrenalectomy for benign adrenal tumors, focusing the attention about cosmetic satisfaction and reduction of postoperative pain. METHODS: Medical records of consecutive patients undergoing LESS adrenalectomy were analyzed. All procedures were performed through a single multichannel port. Demographic and operative data were assessed. A visual analog scale (VAS) was used with a 10-point scale for an objective assessment of incisional pain and incisional cosmesis. RESULTS: Between January 2010 and July 2012, 14 consecutive patients with benign adrenal tumors underwent LESS adrenalectomies. Of the planned LESS adrenalectomies, 12 (86%) were completed with a single-port, whereas two required an additional port placement. Mean operating time was 128.1 ± 31.5 min and mean blood loss 10.5 ± 12.1 ml. Mean pain scores using the VAS on postoperative days 1, 3, and 14 were 2.3, 1.0, and 0.3 points, respectively. The rate of analgesic use was also lower within 12 hours after surgery (14%). The patient was highly satisfied with the single small wound procedure, and mean cosmesis scores of postoperative days 3 and 14 were 9.4 and 9.8 points, respectively. The postoperative course was uneventful with no morbidity within one month of follow-up. CONCLUSIONS: LESS adrenalectomy is a safe and technically feasible procedure for patients with benign adrenal tumors, and offers cosmetic benefit and the potential for postoperative pain reduction. However, surgeons with lack of experience as LESS surgery should be comprehended that the assistance of the needlescopic instrument does not compromise the cosmetic outcomes for difficult cases and the obese patients may not always be suitable candidates for pure LESS technique.